Women's experiences of pregnancy and lactation after bariatric surgery: A scoping review. (July 2022) - Sweet, Linda; Vasilevski, Vidanka
Highlights: Many women of childbearing age are overweight or obese. There is an increasing number of women having bariatric surgery before pregnancy. Bariatric surgery before pregnancy poses risks to the woman and her baby. Women had little knowledge of how the bariatric surgery might impact pregnancy. Women may be conflicted from eating well and maintaining weight loss. Abstract: Background: Obesity is a global public health problem, and in high income countries such as Australia, approximately 60 percent of women are overweight, and half of these women are classed in the obese range. A large proportion of women who are obese are of childbearing age and many are undergoing surgical weight loss procedures (bariatric surgery) before becoming pregnant. Objective: To collate and synthesize available literature regarding women's experiences of pregnancy and/or lactation following bariatric surgery. Design: A scoping review was undertaken of published research between 1990 and 2021, written in English, involving human participants, which described experiences of pregnancy and/or lactation after bariatric surgery. Results: From a total of 4673 abstracts identified using search terms and strings, only 5 items (4 published conference abstracts and one full paper) were identified. Women had little knowledge of how the bariatric surgery might impact pregnancy and only a minority received additional medical/nutrition care during pregnancy. Women wanted more information and support managing their pregnancies, and often received inconsistent advice. For some women experiences of conflict between eating well for the developing fetus and eating little to minimize weight gain or undo the weight loss they had achieved was reported. Conclusions: Ensuring that both health care providers and women are informed about promoting a healthy pregnancy and lactation after bariatric surgery is paramount. More research is required to understand women's experiences and information needs to ensure advice and care is tailored to their specific needs.